KEPATUHAN SUKARELA WAJIB PAJAK DALAM IMPLEMENTASI TAX AMNESTY PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA MAKASSAR UTARA - Erni Cahyani Ibrahim; Ruki Ambar Arum (Jurnal Administrasi Negara, 2018)
To maintain and increase the national income from taxes, special measures or policy breakthroughs are required in order to increase tax revenues in subsequent years and achieve acceptance targets. One of the efforts implemented is the Tax Amendment (Tax Amnesty). From the three phases of tax amnesty held at Kantor Pelayanan Pajak (KPP) Pratama Makassar Utara, it’s known that the taxpayer are quite enthusiastic to follow this program. The high enthusiasm of the taxpayers is a from of voluntary taxpayer compliance implementation. This review is conduct by the researcher on the key elements that are considered capable of realizing voluntary taxpayer complience which include : (1) Good service program to taxpayer, (2) Simple and easy procedure of taxpayer, (3) Complience monitoring program and effective verification, and (4) Enforcement of law enforcement explicitly and fairly. The research method use is descriptive with qualitative approach. Techniques of collecting data is done in depth interviews, observation, and document review. The result show that taxpayer voluntary complience in the implementation of tax amnesty at Kantor Pelayanan Pajak (KPP) Pratama Makassar Utara is effective eve though the target for tax amnesty is not set in the regional scale but centralized (national scale).